Endodontic Management of a Mandibular Second Premolar with Three Root Canals and Taurodontism: A Case Report - Mohammadi, Melika; Zarei, Mina (Iranian Endodontic Journal, 2024)
A complete understanding of canal morphology is essential to achieve successful endodontic treatment. Although mandibular second premolars are reported to have usually only one root canal at the apex, in this case we reported a mandibular second premolar with three root canals and taurodont morphology. A patient was referred to the endodontic department at Mashhad Faculty of Dentistry with a chief complaint of pain in her mandibular right second premolar tooth. The diagnosis of pulpal necrosis and chronic apical periodontitis was established. The initial radiograph showed a taurodont premolar with two roots. However, with cone-beam computed tomography assistance, three root canals were confirmed. The root canal treatment process was successfully managed with a dental operating microscope. Using cone-beam computed tomography and a dental operating microscope greatly facilitated the determination of tooth morphology and successful following nonsurgical endodontic treatment.